Biomechanical differences of arm swing countermovement jumps on sand and rigid surface performed by elite beach volleyball players - Giatsis, G.; Panoutsakopoulos, V.; Kollias, I. A. (Journal of Sports Sciences, 2018)
The purpose of this study was to investigate the possible arm swing effect on the biomechanical parameters of vertical counter movement jump due to differences of the compliance of the take-off surface. Fifteen elite male beach-volleyball players (26.2 ± 5.9 years; 1.87 ± 0.05 m; 83.4 ± 6.0 kg; mean ± standard deviation, respectively) performed counter movement jumps on sand and on a rigid surface with and without an arm swing. Results showed significant (p < .05) surface effects on the jump height, the ankle joint angle at the lowest height of the body center of mass and the ankle angular velocity. Also, significant arm swing effects were found on jump height, maximum power output, temporal parameters, range of motion and angular velocity of the hip. These findings could be attributed to the instability of the sand, which resulted in reduced peak power output due to the differences of body configuration at the lowest body position and lower limb joints` range of motion. The combined effect of the backward arm swing and the recoil of the sand that resulted in decreased resistance at ankle plantar flexion should be controlled at the preparation of selected jumping tasks in beach-volleyball.